PERANAN KEPERCAYAAN SEBAGAI VARIABEL PEMODERASI PENGARUH ANTARA TEKANAN WAKTU DAN KOMPLEKSITAS TERHADAP PENILAIAN DAN PENGAMBILAN KEPUTUSAN DALAM AUDIT - Septony B. Siahaan; Arthur Simanjuntak (Sekolah Tinggi Ilmu Ekonomi-LMII Medan, 2021)
This study aims to assess the moderating effect of Trust the joint influence between time pressure and complexity on Judgment and Decision-Making in Auditing. Behavioral Decision Theory (BDT) is used from a retaining heuristic perspective. The method used is an experimental method with a final sample of 36 independent auditors. For analysis, t test and multiple linear regression were used. The results of the analysis can be concluded that factors such as trust, time pressure, and complexity, partially and simultaneously, affect Judgment and Decision-Making in Auditing. This study shows that trust is able to moderate (strengthen) the joint influence of time pressure and complexity on Judgment and Decision-Making in Auditing. Time pressure and task complexity have a positive effect on Judgment and Decision-Making in Auditing, but when including trust as a moderating factor, the effect of time pressure and complexity can reduce auditor difficulties and uncertainty in Judgment and Decision-Making in Auditing.